2017
DOI: 10.1097/md.0000000000007253
|View full text |Cite
|
Sign up to set email alerts
|

Association between KCNE1 G38S gene polymorphism and risk of atrial fibrillation

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Numerous studies have investigated the role of the KCNE1 gene in AF. Jiang et al [17] conducted a metaanalysis of a total of 14 independent case-control studies involving 2,810 patients and 3,080 healthy controls. They concluded that the G38S polymorphism in the KCNE1 gene could significantly increase the risk of AF in both Chinese and Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the role of the KCNE1 gene in AF. Jiang et al [17] conducted a metaanalysis of a total of 14 independent case-control studies involving 2,810 patients and 3,080 healthy controls. They concluded that the G38S polymorphism in the KCNE1 gene could significantly increase the risk of AF in both Chinese and Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a shortened ERP within atrial cardiomyocytes might contribute to the development of multiple-circuit reentry that can predispose to a form of AF [15]. Polymorphism in the KCNE1 gene (G38S) increases the risk of AF significantly in both Chinese and Caucasian populations [17], suggesting the importance of KCNE1 gene in the predisposition to AF. It has also been reported that the minor allele of rs2236609 in KCNE1 trends toward significance with a longer QTc, which increases the risk of irregular heartbeat [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have suggested that genetic factors play an important role in AF occurrence and development [9]. In fact, common genetic variants (a multitude of single-nucleotide polymorphisms [SNPs]) associated with AF have been detected in genome-wide association studies (GWASs) [10][11][12], such as endothelial nitric oxide synthase 786T/C, CYP11B2 rs1799998, KCNE1 G38S, and caveolin-1 rs3807989 [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, many evidences support that genetic factors play an important role in its occurrence and development [9]. In fact, common genetic variants (a multitude of single-nucleotide polymorphism, SNPs) associated with AF have been detected in Genome-wide association studies (GWAS) [10][11][12]: such as endothelial nitric oxide synthase 786T/C, CYP11B2 rs1799998, KCNE1 G38S, Caveolin-1 rs3807989 [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%